2021
DOI: 10.1039/d1ra01468d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PEMFC durability with graphitized carbon black cathode catalyst supports under accelerated stress testing

Abstract: The enhanced anti-corrosion properties of graphitized carbon substrates are evaluated via accelerated stress tests (ASTs). The graphitized surface properties of carbon are responsible for alleviating the coarsening and agglomeration of Pt particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
4
3
Order By: Relevance
“…73 The results reported here are thus superior to earlier reports in the literature. 35,73 A performance degradation of 50 mV for PtSn/VC(3) after 60 000 cycles is remarkable as a maximum degradation of 30 mV is the target set by the US Department of Energy after 30 000 cycles. 32…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…73 The results reported here are thus superior to earlier reports in the literature. 35,73 A performance degradation of 50 mV for PtSn/VC(3) after 60 000 cycles is remarkable as a maximum degradation of 30 mV is the target set by the US Department of Energy after 30 000 cycles. 32…”
Section: Resultscontrasting
confidence: 65%
“…73 The results reported here are thus superior to earlier reports in the literature. 35,73 A performance degradation of 50 mV for PtSn/VC(3) after 60,000 cycles is remarkable as a maximum degradation of 30 mV is the target set by the US Department of Energy after 30,000 cycles. 32 It is thus apparent that alloying Pt with Sn leads to superior electrocatalytic activity for the electrooxidation of molecular hydrogen and the electroreduction of molecular oxygen at the anode and cathode of the fuel cell, respectively.…”
Section: Rsc Sustainability Accepted Manuscriptcontrasting
confidence: 65%
See 1 more Smart Citation
“…At present, carbon black materials (such as Ketjen Black and Vulcan XC-72, etc.) have been widely used as PEMFC catalyst supports due to their advantages of high conductivity, high active area, porous structure, good stability in acidic and alkaline media, and relatively low price [ 49 , 108 , 129 ]. However, in the case of PEMFCs running for a long time, the charcoal supports easily form oxygen-containing groups on the catalyst support surface, which will reduce the conductivity of the catalyst and lead to serious sintering of catalyst NPs.…”
Section: Controllable Preparation Of Pt-based Orr Catalystsmentioning
confidence: 99%
“…The carbon support treated at 1600 • C showed the highest durability, indicating that the graphitization degree of support is the key factor for development of a high durability catalyst. Xue [44] et al compared the ORR activity of Ketjenblack EC-600 as catalyst support with original EC-600 as catalyst and JM60% catalyst after high temperature heat treatment at 1600 • C and 1800 • C. The results showed that the initial particle size of the prepared catalyst ranged from 2.80 to 3.09 nm. After start-stop protocol testing, the particle size of Pt/EC-600 increased from 2.80 to 5.31 nm, and the particle size of Pt/EC-G1800 had the minimum increase in particle size, from 2.99-3.65 nm.…”
Section: Introductionmentioning
confidence: 99%